Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 1 - Section 1.1 - Four Ways to Represent a Function - 1.1 Exercises - Page 21: 30



Work Step by Step

$\frac{f(x)-f(1)}{x-1}=\frac{\frac{x+3}{x+1}-\frac{1+3}{1+1}}{x-1} =\frac{(x+3)-2(x+1)}{(x-1)(x+1)} =\frac{x+3-2x-2}{(x-1)(x+1)} =-\frac{x-1}{(x-1)(x+1)} =-\frac{1}{x+1}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.